(untitled) (CIPEEX, 2025)
Abstract: The document discusses the development of the Smart Health project, whose main objective is to promote people’s health and well-being in alignment with the United Nations Sustainable Development Goals (SDGs). The project focuses on creating an application and website that offer users features aimed at improving their quality of life, including services such as professional health advice, psychological support, and personalized diets. The methodology used in the platform’s construction prioritizes security and reliability, aiming to ensure user satisfaction and continuous engagement. To make the software accessible to everyone, the project includes inclusive features, such as audio descriptions for visually impaired individuals and support for people with different dietary needs. The method adopted for the software’s creation involved extensive research on the main challenges faced in the health sector and feedback from professionals and potential users. The study also analyzed the key factors negatively affecting physical and psychological well-being to offer solutions that prevent issues such as obesity, chronic diseases, and emotional disorders. The expected results include creating an accessible platform that motivates users to adopt healthy habits and seek specialist help when needed. The project concludes that by providing a reliable and inclusive experience, Smart Health can improve many lives, encouraging people to better care for their physical and mental health.